Limitation of Opinion With Social Media Take Down System, is Indonesia Toward to Totalitrism? - Harrel Ciddan; Ailsa Fitri Shafwa; Abim Prima Prayoga; Navita Fayola Frihanggrahita; Fakhris Aulady; Ali Imron (Metafora: Education, Social Sciences and Humanities Journal, 2022)
Indonesia is a country with a democratic government system so that Indonesia provides equal treatment, rights and obligations to all its people. Freedom of opinion is a right owned by every human being that is guaranteed by a state, as contained in Article 28E paragraph (3) which reads "Everyone has the right to freedom of association, assembly and expression". Advances in technology and information today is the right opportunity for every individual to voice his opinion on social media. Nevertheless. Freedom of argument often raises problems, namely the restriction of opinion by implementing a take down system on social media. This restriction of opinion then becomes a question mark, is Indonesia then heading towards totalitarianism? The method used in this article is a literature study, with data collection techniques through reference searches through books, journals, notes, and reports that are related to the problem. This article aims to describe the practice of restricting opinions that are taken down in social media. In addition, this article is expected to provide solutions to these problems. Restrictions on opinion on social media can still be found, this is supported by the presence of two examples of cases of opinion that were taken down on social media without any information. One form of unilateral take down that happened to Surya Anta when explaining the conditions of the Detention Center in a thread on his twitter.